Mongolia’s external environment: current status and future trends of regional and multilateral cooperation - Tsend, Baatar; Baatar, Battogtokh (Mongolian Journal of International Affairs, 2020)
Today, the economic globalization is staging and regional trade and economic integration is gaining strength. This trend is more accelerated from the proportion of the COVID-19 pandemic in 2020. In this context, the countries revised their foreign policies and determined their priorities for cooperation. In this article, Author analyzes the political and economic environment of Mongolia and the main tendencies of its foreign trade and economic cooperation with other countries, including Asian and neighboring countries.